EVALUATION OF QTC INTERVAL IN CIRRHOSIS PATIENTS WITH VARICEAL HEMORRHAGE - Rezan Karaali; Umut Payza; Ahmet Kayalı; Firdevs Topal; Fatih Esad Topal (İstanbul Tıp Fakültesi Dergisi)
Objective: In this study, we investigated the effect of the QTc interval in cirrhosis patients on mortality and morbidity in esophageal variceal hemorrhages. Material and Method: It was retrospectively scanned in a single-centred design. The QTC intervals before and during the bleeding were calculated. The demographic characteristics and mortality status were recorded. Results: Bleeding was detected in 117 of the 156 patients. A total of 83% of these were male, and 17% were female. The QTc interval in these patients measured at the time of bleeding was longer than that measured before bleeding (p<0.001). The QTc interval of the patients who died due to bleeding was found to be 509.9 ms. It was calculated for males as 520.6 ms, and 487.4 ms for females. In the ROC analysis that was conducted for the QTc in terms of mortality, the sensitivity was 82.4% and specificity was 79.7% for 464.0 ms in males (AUC:0.785; 95% CI 0.724-0.825). The sensitivity was 77.8% and the specificity was 90.0% for QTc’s 454.0 ms cutoff value for females (AUC:856; 95% CI 0.812-0.862). Conclusion: The QTc interval is prolonged in the case of esophageal variceal hemorrhage in patients diagnosed with cirrhosis. A prolonged QTc interval is associated with mortality and morbidity of patients.